Single‐cell transcriptome analysis revealed the heterogeneity and microenvironment of gastrointestinal stromal tumors - Mao, Xiaofan (Cancer Sci, 2021)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the human gastrointestinal tract. In this study, we performed single‐cell RNA sequencing (RNA‐seq) on intra‐ and peri‐tumor tissues from GIST patients with the aim of discovering the heterogeneity of tumor cells in GIST and their interactions with other cells. We found four predominating cell types in GIST tumor tissue, including T cells, macrophages, tumor cells, and NK cells. Tumor cells could be clustered into two groups: one was highly proliferating and associated with high risk of metastasis, the other seemed “resting” and associated with low risk. Their clinical relevance and prognostic values were confirmed by RNA‐seq of 65 GIST samples. T cells were the largest cell type in our single‐cell data. Two groups of CD8(+) effector memory (EM) cells were in the highest clonal expansion and performed the highest cytotoxicity but were also the most exhausted among all T cells. A group of macrophages were found polarized to possess both M1 and M2 signatures, and increased along with tumor progression. Cell‐to‐cell interaction analysis revealed that adipose endothelial cells had high interactions with tumor cells to facilitate their progression. Macrophages were at the center of the tumor microenvironment, recruiting immune cells to the tumor site and having most interactions with both tumor and nontumor cells. In conclusion, we obtained an overview of the GIST microenvironment and revealed the heterogeneity of each cell type and their relevance to risk classifications, which provided a novel theoretical basis for learning and curing GISTs.